2017
DOI: 10.3390/cryst7110348
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication Challenges for Millimeter-Scale Three-Dimensional Phononic Crystals

Abstract: While phononic crystals can be theoretically modeled with a variety of analytical and numerical methods, the practical realization and comprehensive characterization of complex designs is often challenging. This is especially important for the nearly limitless possibilities of periodic, three-dimensional structures. In this contribution, we take a look at these design and fabrication challenges of different 3D phononic elements based on recent research using additive manufacturing. Different fabrication techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…metamaterials with complex geometries[48][49][50][51]. AM technologies create structures in a layer-by-layer process, either through material deposition or by selective solidification of a feedstock.…”
mentioning
confidence: 99%
“…metamaterials with complex geometries[48][49][50][51]. AM technologies create structures in a layer-by-layer process, either through material deposition or by selective solidification of a feedstock.…”
mentioning
confidence: 99%
“…The correlation between the frequency of the cavity mode and its bandwidth and material parameters of a liquid confined in the cavity is the basic idea behind the application of phononic crystals as a sensor platform. Lucklum et al, 2012;Zubtsov et al, 2012;Oseev et al, 2013;Salman et al, 2014;Li et al, 2015;Wang et al, 2016;Villa-Arango et al, 2017a;Villa-Arango et al, 2017b;Lucklum and Vellekoop, 2017;Oseev et al, 2017;Lucklum and Vellekoop, 2018;Villa-Arango et al, 2018;Cicek et al, 2019;Lucklum and Vellekoop, 2019;Wasmer et al, 2019 referred to recently published articles applying this methodology. We also want to refer to a different kind of PnC sensor with incidence normal on the periodic structure [ (Zubtsov et al, 2012), (Lucklum et al, 2012), (Lanoy et al, 2018)].…”
Section: The Role Of Materials Propertiesmentioning
confidence: 99%
“…Lucklum et al . 25 discussed the manufacturing challenges of 3D PCs and showed that additive manufacturing (AM) has the fabrication capabilities required for the realisation of geometrically complex 3D PCs 2629 . There are a wide variety of AM technologies that may be used to manufacture PC materials, such as laser powder bed fusion (LPBF), photo-polymerization, stereolithography and inkjet printing 3033 .…”
Section: Introductionmentioning
confidence: 99%